Application research of the partial discharge automatic detection device and diagnostic method based on the ultrasonic in long distance GIL equipment. Issue 5 (June 2019) - Wei, Xu; Teng, Yun; Liu, Zi-quan; Deng, Jie-qing; Jia, Yong-yong
Abstract: Gas-insulated transmission lines are very long with the length over 100 meters for each single chamber and there are no non-metal connection parts between two chambers, which leads to a poor detect effect when using the UHF method. Because of the attenuation of the propagation process, the ultrasonic detection method has many measuring points and a large workload of manual detection. To solve these problems, an automatic detection device and diagnostic location method based on ultrasonic method for the partial discharge of GIL were proposed in this paper. By combining the ultrasonic partial discharge detection device with the inspection robot, the robot performs the partial discharge inspection and transmits the data to the background diagnostic system for analysis. The overall structure of the system, the method of automatic diagnostic and location are introduced. The effectiveness of detection, diagnostic and location of the system is verified by simulation of the discharge signal in the laboratory. The application of the system can avoid the possible limitations of manual inspection in GIL Partial Discharge Ultrasonic testing, improve the work efficiency and guarantee the safe operation of power system.